Field notes contributed by Hank Zaletel and Linda Zaletel, spring 1980 - Zaletel, Hanket al; Zaletel, Lindaet al (1980)
List of birds and locations contributed by Hank Zaletel and Linda Zaletel. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed